Mid Holocene human adaptation at the Ras al Jinz 3 site: The late neolithic to the early bronze age lithics of coastal Oman from a traceological and technological perspective - Hilbert, Yamandú H.; Clemente-Conte, Ignacio; de Rorre, Alexandre; Azzarà, Valentina M. (Journal of Archaeological Science: Reports, 2025)
The south-eastern Arabian coastline, with its diverse habitats and high levels of bio productivity, is characterised by an abundance of archaeological sites spanning from the Neolithic to the Islamic periods. Since the Early Holocene, populations of hunters, fishers, herders, and gatherers developed cultural and behavioural knowledge that allowed them to flourish and endure the climatic fluctuations affecting the region. Here we present the results of the traceological, typological and technological analysis undertaken on a sample of lithic artefacts dating to the Late Neolithic and Early Bronze Age from the multi occupational site of Ras Al Jinz RJ-3 on the Omani coast. The site presents multiple archaeological horizons, dated by radiocarbon, each associated with stone tools marked by diverging techno-typological and functional patterns, indicating that different activities were performed through the Mid and Late Holocene. During the Late Neolithic (c. 4200–3200 BCE) a high diversity of functional and behavioural patterns was identified. The first part of the Early Bronze Age (EBA) (Hafit period, c. 3200–2600 BCE) is characterized by an increase in diversification and ad-hoc use of stone tools for diverse activities such as cutting, scraping and drilling. Finally, the second part of the EBA (Umm an-Nar period, c. 2600–2000 BCE) shows a strictly task oriented pattern dominated by the manufacture of Conus shell rings. Our results further strengthen the interpretation of the site as being the center of different and specific task activities throughout the Mid-Late Holocene period.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Coastal archaeology; Early Bronze Age; Late Neolithic; Oman; Stone tools; Traceology